Mortality in Brazil according to gender perspective, years 2000 and 2010 - Erly Catarina de Moura; Wallace dos Santos; Alice Cristina Medeiros das Neves; Eduardo Schwarz; Romeu Gomes
ABSTRACT: Objective: The article assessed the overall mortality in Brazil in 2000 and 2010. Methods: Data source was the Mortality Information System from Ministry of Health of Brazil. Results: The data show the high rate of mortality among men compared to women between ages of 20 to 59 years and an expressive lower life expectancy by this population. The main groups of death were: external causes; diseases of the circulatory system, diseases of the digestive system, infectious and parasitic diseases, diseases of the respiratory system; mental and behavioral disorders; diseases of the nervous system; endocrine, nutritional and metabolic diseases; neoplasia and diseases of the genitourinary system. Conclusion: Unequal gender relations and distinct characteristics of exposure to risk factors can explain this mortality, highlighting the need to bring critical incorporation of relational gender perspective by public health policies.